2013
DOI: 10.1128/aem.03693-12
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Expression of Genes Involved in the Conversion of Daidzein and Genistein by the Equol-Forming Bacterium Slackia isoflavoniconvertens

Abstract: Gut bacteria play a key role in the metabolism of dietary isoflavones, thereby influencing the availability and bioactivation of these polyphenols in the intestine. The human intestinal bacterium Slackia isoflavoniconvertens converts the main soybean isoflavones daidzein and genistein to equol and 5-hydroxy-equol, respectively. Cell extracts of S. isoflavoniconvertens catalyzed the conversion of daidzein via dihydrodaidzein to equol and that of genistein to dihydrogenistein. Growth of S. isoflavoniconvertens i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
134
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(140 citation statements)
references
References 30 publications
4
134
2
Order By: Relevance
“…Wild-type DHDR has a catalytic efficiency that is higher by a factor of about 23.5 for (S)-DHD than for (R)-DHD in terms of the k cat /K m ratio. We confirmed that DHDR prefers (S)-DHD to (R)-DHD as its substrate (9,13).…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…Wild-type DHDR has a catalytic efficiency that is higher by a factor of about 23.5 for (S)-DHD than for (R)-DHD in terms of the k cat /K m ratio. We confirmed that DHDR prefers (S)-DHD to (R)-DHD as its substrate (9,13).…”
Section: Resultssupporting
confidence: 70%
“…Although DHDRs from S. isoflavoniconvertens (13) and Lactococcus sp. strain 20-82 (10) were previously characterized based on their kinetic parameters, cofactor specificity, and preference for (S)-DHD, the analyses were restricted only to neutral pH, which prohibited a complete understanding of DHDR's characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene cloned in pPSG-IBA 3 or pPSG-IBA 5 was expressed in E. coli KRX following induction by rhamnose (0.1% [wt/vol]) and cultivation overnight at 25°C. Purification of tagged proteins from cell extracts was done using a 1-ml Strep-Tactin Sepharose column (IBA) as described previously (21).…”
Section: Chemicals (ϯ)-Taxifolin and (ϯ)mentioning
confidence: 99%
“…The reported isoflavone metabolites were utilized for various metabolomic studies to investigate correlations among host physiology, host metabolism, and gut microbiota changes (Lee et al 2012;Kobayashi et al 2013). The genes involved in the biotransformation of daidzein and the metabolites were also cloned from the isolated intestinal bacteria for the biochemical research (Shimada et al 2010;Tsuji et al 2012;Schröder et al 2013). Therefore, the isolation of new intestinal bacteria and characterization of the catalytic properties are of great significant.…”
Section: Discussionmentioning
confidence: 99%